2015
DOI: 10.1155/2015/481945
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Scoliosis Surgery: A Novel Technique in Patients with Neuromuscular Scoliosis

Abstract: Minimally invasive surgery (MIS) has been described in the treatment of adolescent idiopathic scoliosis (AIS) and adult scoliosis. The advantages of this approach include less blood loss, shorter hospital stay, earlier mobilization, less tissue disruption, and relatively less pain. However, despite these significant benefits, MIS approach has not been reported in neuromuscular scoliosis patients. This is possibly due to concerns with longer surgery time, which is further increased due to more levels fused and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…2 Such approaches are rarely reported in neuromuscular scoliosis patients. 3 Our aim is to develop a minimally invasive approach for insertion of a strong and stable construct capable of further adjustments and avoidance of final fusion.…”
mentioning
confidence: 99%
“…2 Such approaches are rarely reported in neuromuscular scoliosis patients. 3 Our aim is to develop a minimally invasive approach for insertion of a strong and stable construct capable of further adjustments and avoidance of final fusion.…”
mentioning
confidence: 99%
“…Traditional open techniques are considered the gold standard for the surgical management of scoliosis, though as minimally invasive spine surgery is becoming more widely practiced it is being increasingly applied to pediatric deformity correction. [15][16][17][18][19][20] This meta-analysis was conducted to evaluate the differences in outcomes between open and MIS deformity correction and found that MISS is associated with less blood loss but longer operative times compared to traditional open fusion for AIS, while demonstrating similar outcomes in terms of curve correction, postoperative pain, LOS, and complications/reoperations. MISS is emerging as a feasible tool in deformity correction, particularly in adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…8 , 14 A modification of it was described to adapt for NMS cases which need longer instrumentations and usually present with more rigid curves. 11 We used a single midline skin incision extending from upper to lower instrumented vertebra and following the spinous processes. No fluoroscopy was used to determine the length and localization of it.…”
Section: Methodsmentioning
confidence: 99%
“…Only one retrospective comparative series including 24 patients and one surgical technique paper including two case reports have been published up to date. 11 , 12 Both publications reported a lower EBL in comparison to the posterior midline approach and the surgical technique paper showed additionally a shorter intensive care unit (ICU) and hospital LOS.…”
Section: Introductionmentioning
confidence: 99%